Effect of Epilepsy on Sleep Quality During Pregnancy and Postpartum. (11th October 2022) - Toprani, Sheela; Meador, Kimford J.; Robalino, Chelsea P.; Brown, Carrie Anne; Matthews, Abigail G.; Gerard, Elizabeth E.; Penovich, Patricia; Gedzelman, Evan; Cavitt, Jennifer; Hwang, Sean T.; Kalayjian, Laura A.; Sam, Maria; et al.
Abstract : Background and Objectives: This study seeks to understand how sleep is affected in pregnant women with epilepsy (WWE) relative to healthy pregnant women during pregnancy and postpartum and to nonpregnant WWE during comparative periods. Sleep affects maternal health and mood during pregnancy. Maternal sleep disturbances are related to poor fetal growth and increased fetal deaths. Epilepsy is the most common neurologic condition in pregnancy. Sleep disruption can worsen epileptic seizures. The interplay between epilepsy, pregnancy, and sleep is poorly understood. Methods: The Maternal Outcomes and Neurodevelopmental Effects of Antiepileptic Drugs (MONEAD) study is an NIH-funded, prospective, observational, multicenter study, enrolling women from December 2012 through January 2016. Sleep quality was assessed using the average Pittsburgh Sleep Quality Index collected during pregnancy, postpartum, or analogous periods. Sleep scores range from 0 to 21 with higher scores indicating worse sleep quality; scores >5 are associated with poor sleep quality. Results: Of 351 pregnant WWE, 105 healthy pregnant women, and 109 nonpregnant WWE enrolled in the MONEAD study, data from 241 pregnant WWE, 74 healthy pregnant women, and 84 nonpregnant WWE were analyzed. Pregnant WWE had worse sleep (a higher mean sleep score) during pregnancy compared with healthy pregnant women in unadjusted analysis ( p = 0.006), but no longer significant in adjusted analysis ( p = 0.062); pregnant WWE (least square mean sleep score [95% CI] = 5.8 [5.5–6.1]) vs healthy pregnant women (5.1 [4.6–5.7]). During postpartum period, WWE (5.6 [5.4–5.9]) had similarly impaired sleep compared with healthy women (5.7 [5.2–6.2]; adjusted p = 0.838). Sleep was significantly worse in pregnant WWE vs nonpregnant WWE (for comparable period) in pregnancy and postpartum in unadjusted and adjusted analyses; adjusted scores for pregnant WWE in pregnancy (5.7 [5.4–6.0]) and those in postpartum (5.7 [5.4–6.0]) compared with those for nonpregnant WWE (4.7 [4.2–5.3]; p = 0.002) and (4.1 [3.6–4.7]; p < 0.001), respectively. Sleep quality between pregnancy and postpartum varied only in healthy pregnant women (change in mean score = 0.8 [0.2–1.3]; p = 0.01), whose sleep was worse in postpartum. Discussion: Pregnant WWE had worse sleep during pregnancy and postpartum period than nonpregnant WWE during comparable periods in the adjusted analysis. Trial Registration Information: The study is registered at ClinicalTrials.gov as NCT01730170.